Original paper Surgical excision and cryosurgery in the treatment of recurrent auricular keloids - Zieliński, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Keloids result from an abnormal fibrous wound healing process. Effective treatment of keloids still present a significant challenge. Various modalities of therapy may be applied, but none of them has been proved entirely successful. Aim: To evaluate the effectiveness of cryosurgery as a preventive approach after surgical excision of the recurrent auricular keloids. Material and methods : Eight patients treated for recurrent auricular keloid were included in the study. The recurrence followed surgical excisions without any complementary therapy. The keloids were excised under local anaesthesia within healthy tissue borders. Cryosurgery was applied on the seventh or tenth day following the excision, after the removal of sutures. Results : Accepting the lack of recurrence after the treatment as the main criterion, good results were obtained in 7 out of 8 treated patients, which was 87.5% of the study group. Conclusions : Cryosurgery is a very effective approach preventing keloid recurrence after surgical excision; this finding is supported by 87.5% of good results in the treatment of recurrent changes. The effectiveness of this method may result from the specific location of the changes and a relatively small surface of tissue subjected to freezing, which enables complete damage of keloids and formation of atrophic scars on these areas.